THE EFFECT OF VISUALIZATION AND MOTOR ABILITY TO THE LEARNING OUTCOMES BADMINTON SKILLS - Puspitorini, Wahyuningtyas; Tangkudung, James A.P. (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
This study aims to determine: (1) the effect of conventional teaching methods and visualization of the learning outcomes badminton skills, (2) the effect of high and low motor ability to the learning outcomes badminton skills, (3) interaction with motor ability teaching methods to the learning outcomes badminton skills. This research uses experimental methods to design 2 x 2 factorial design number of samples in this study were 61 students. Data collection techniques with a series of skills tests badminton. Data analysis technique is the analysis of variance (ANOVA) on Âµ = 0.05 significance level. The study concluded that: (1) there is no difference in the effect of conventional teaching methods and visualization of the learning outcomes of badminton skills, but special on short service skills there are significant differences. (2) there is no difference in the effect of high and low motor ability to the learning outcomes badminton skills, (3) there is no interaction with motor ability teaching methods to the learning outcomes badminton skills.